1997
DOI: 10.1038/sj.leu.2400698
|View full text |Cite
|
Sign up to set email alerts
|

Functional assay of multidrug resistant cells using JC-1, a carbocyanine fluorescent probe

Abstract: Multidrug resistance (MDR) is characterized by a decrease inof anthracyclines (N-acetyl-daunorubicin) or vinca-alkaloids the efficiency of chemotherapeutic agents correlated with the (vindoline), steroids (progesterone), and other lipophilic catexpression and activity of a membrane protein: the ionic molecules (amiodarone, dipyridamole, S9788 5 ) (for permeability-glycoprotein (Pgp 170). Clinically, detection of reviews see Refs 6 and 7). Some compounds including verapa-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 3 publications
0
43
0
Order By: Relevance
“…The dye enters living cells and fluoresces bright red in its multimeric form within active mitochondria. In apoptotic cells, the mitochondrial membrane potential collapses, and the JC-1 dye does not manifest its multimeric form within the mitochondria, thus remaining in the cytoplasm in its green J-monomeric form (Kuhnel et al 1997). We verified that DREF over-expression under the GMR-GAL4 driver induces apoptosis in eye imaginal disc cells (Fig.…”
Section: Dref Is a Key Regulator For Dant Promoter Activity In Livingmentioning
confidence: 54%
“…The dye enters living cells and fluoresces bright red in its multimeric form within active mitochondria. In apoptotic cells, the mitochondrial membrane potential collapses, and the JC-1 dye does not manifest its multimeric form within the mitochondria, thus remaining in the cytoplasm in its green J-monomeric form (Kuhnel et al 1997). We verified that DREF over-expression under the GMR-GAL4 driver induces apoptosis in eye imaginal disc cells (Fig.…”
Section: Dref Is a Key Regulator For Dant Promoter Activity In Livingmentioning
confidence: 54%
“…However, using K562 cell lines with increasing levels of resistance, we demonstrated that the level of JC-1 accumulation correlated with the level of P-gp expression as detected by UIC2 antibodies (8). Also, in AML patients, JC-1 was shown to be able to discern between three groups of patients: resistant, intermediate, and sensitive (9).…”
Section: Discussionmentioning
confidence: 84%
“…With JC-1, the sensitive cell lines display both green and red fluorescence. In resistant cells, with the increase of P-gp activity the green fluorescence of JC-1 decreased, and the red fluorescence was lost completely (8). Our study thus proved JC-1 to be a very sensitive probe, more sensitive than Rhodamine 123 (Rh 123), for the detection of low-level P-gp activity in adult patients with acute myeloid leukemia (AML).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…32 Verapamil pretreatment did not affect fluorescence in LoVo WT cells, while the emitted fluorescence was significantly increased in MDR cells.…”
Section: Flow Cytometrymentioning
confidence: 85%